2021
DOI: 10.1039/d1na00154j
|View full text |Cite
|
Sign up to set email alerts
|

MoS2and Janus (MoSSe) based 2D van der Waals heterostructures: emerging direct Z-scheme photocatalysts

Abstract: Two-dimensional (2D) materials viz. transition metal dichalcogenides (TMD) and transition metal oxides (TMO) offer a platform that allows creation of heterostructures with a variety of properties. The optoelectronic industry has...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 82 publications
(107 reference statements)
2
23
0
1
Order By: Relevance
“…The calculated DE band bending values are less than 0, suggesting electron transfer from the heterostructure to the monolayer. 93 We observed that DE band bending of the GeI 2 monolayer was more negative compared to that of the C 2 N. Therefore, the net Lo ¨wdin population charge on the GeI 2 monolayer is positive, consistent with the CDD and work function results. Another critical element in constructing photocatalytic devices is optical absorption.…”
Section: Energy Advancessupporting
confidence: 88%
“…The calculated DE band bending values are less than 0, suggesting electron transfer from the heterostructure to the monolayer. 93 We observed that DE band bending of the GeI 2 monolayer was more negative compared to that of the C 2 N. Therefore, the net Lo ¨wdin population charge on the GeI 2 monolayer is positive, consistent with the CDD and work function results. Another critical element in constructing photocatalytic devices is optical absorption.…”
Section: Energy Advancessupporting
confidence: 88%
“…[49][50][51] Furthermore, graphene is considered as one of the key components of many vdWHs due to its high carrier mobility of 2 Â 10 5 cm V À1 s À1 , the good thermal conductivity of 5.5 Â 10 3 W m À1 K À1 and adjustable work function. 52,53 Nowadays, other graphene-like materials have also been developed, such as molybdenum disulde (MoS 2 ), 54,55 molybdenum diselenide (MoSe 2 ), 56,57 tin selenide (SnSe), [58][59][60] bismuth telluride (Bi 2 Te 3 ), 61 tungsten diselenide (WSe 2 ), 62 black phosphene (BP) 63,64 and hexagonal boron nitride (HBN). 65 The atoms in each layer (in-plane) of these vdW materials are held together by covalent bonds, while the atomic layers (out-of-plane) without hanging bonds are held together by weak vdW interactions.…”
Section: The Construction Of Vdwhsmentioning
confidence: 99%
“…Nowadays, other graphene-like materials have also been developed, such as molybdenum disulfide (MoS 2 ), 54,55 molybdenum diselenide (MoSe 2 ), 56,57 tin selenide (SnSe), 58–60 bismuth telluride (Bi 2 Te 3 ), 61 tungsten diselenide (WSe 2 ), 62 black phosphene (BP) 63,64 and hexagonal boron nitride (HBN). 65 The atoms in each layer (in-plane) of these vdW materials are held together by covalent bonds, while the atomic layers (out-of-plane) without hanging bonds are held together by weak vdW interactions.…”
Section: Theoretical Basis and Establishment Of Vdwhsmentioning
confidence: 99%
“…[16][17][18][19] While for other materials whose bandgaps are in the range of 1.8-2.8 eV, they may be possibly applied in the field of photocatalytic reaction under visible light. [20][21][22] Besides bandgap, band alignment is another important characteristic that determines the material application. [23][24][25][26] For instance, in the fields of photovoltaics and photocatalysis, heterojunctions with the type-II band alignment are preferred since the recombination rates for electrons and holes are relatively slow.…”
Section: Introductionmentioning
confidence: 99%